Lexicography of Coronavirus-related Neologisms - Klosa-Kückelhaus, Annette; Kernerman, Ilan (Lexicographica. Series Maior, 2022)
This volume brings together contributions by international experts reflecting on Covid19-related neologisms and their lexicographic processing and representation. The papers analyze new words, new meanings of existing words, and new multiword units in as many as ten languages, considering both specialized and general language, monolingual as well as bilingual and printed as well as online dictionaries.